1994
DOI: 10.1203/00006450-199409000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Increased Left Ventricular Output during In Utero Ventilation in Fetal Sheep

Abstract: A model of in utero ventilation was used to elucidate the mechanisms by which left ventricular (LV) output increases with the transition from a fetal to a neonatal circulation. Using a conductance catheter, LV volumes were measured in seven anesthetized, near-term fetal sheep. Pressure-volume data was recorded before and with oxygen ventilation and again after occlusion of the umbilical cord. Ventilation caused increases in LV end-diastolic volume (2.3 2 0.9 to 2.9 2 0.6 mL/kg; p < 0.05), stroke volume (1.2 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Just before lung ventilation (90% of incubation, or day 19) the E A /E LV ratio is 1 in the normoxia-incubated chicken fetus (Table 3), which is similar to normal values in healthy adult mammals at rest and in fetal lambs (7,25). This suggests that mechanical efficacy and energetic efficiency are balanced similarly in fetal chickens as in adult and fetal mammals.…”
Section: Arterial-cardiac Couplingsupporting
confidence: 61%
“…Just before lung ventilation (90% of incubation, or day 19) the E A /E LV ratio is 1 in the normoxia-incubated chicken fetus (Table 3), which is similar to normal values in healthy adult mammals at rest and in fetal lambs (7,25). This suggests that mechanical efficacy and energetic efficiency are balanced similarly in fetal chickens as in adult and fetal mammals.…”
Section: Arterial-cardiac Couplingsupporting
confidence: 61%
“…Second, inspiration in human fetuses [6] and intrauter ine ventilation in fetal lambs [3,5,7] are associated with an increase in left ventricular stroke volume. Such an increase can be due to an increase in ejection fraction, end-diastolic volume, or both.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in ejection fraction may be caused by an increase in contractility or a reduction in afterload. However, afterload actually in creases during respiration [3], and contractility does not change at a time when left ventricular output almost dou bles [7], Therefore, the ejection fraction does not seem to change during respiration, so that the inspiration-associ ated increase in stroke volume is likely to be caused by an increase in left ventricular end-diastolic volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With parallel circulation, fetal hemodynamics are distinct from their postnatal occurrences (6). Several studies indicated the fetal ventricle is sensitive to cardiac load changes (7,8). Obstruction to cardiac outflow in fetuses with TOF might ultimately lead to myocardial impairment in utero and may also influence the postnatal outcome and interventional timing.…”
Section: Introductionmentioning
confidence: 99%